HYDROGEOLOGICAL CONDITIONS OF THE UPPER STREAMS OF THE VEDI RIVER AND ASSESSMENT OF GROUNDWATER NATURAL RESOURCES OF THE JERMANIS SPRINGS WATERSHED (Proceedings of the YSU C: Geological and Geographical Sciences, 2022)
The work is devoted to assessment of components of groundwater runoff on the example of the Jermanis springs located in the upper streams of the Vedi River. The strictly changeable nature of the flow of springs is envisaged by the close proximity of recharge and discharge zones. The cartographic materials used in work were analyzed in the same geographic coordinate system, as well as a comparison of chemical analyzes of groundwater with archival data has been conducted. An assessment of the geoecological conditions and evaluation of natural resources of groundwater has been accomplished. It is recommended to apply the described method to assess groundwater run-off in river basins with similar natural and climatic conditions, for example, for the river basins of the Azat, Argichi, Vorotan, etc.
Keywords: groundwater run-off; deep run-off; groundwater natural resources